2018
DOI: 10.1155/2018/6706413
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Soil-Transmitted Helminthiasis in Preschool Children Living in Farmland, North Sumatera, Indonesia

Abstract: Background Disease burden from soil-transmitted helminthiasis (STH) is mainly attributed to its chronic and insidious impact on health and quality of life. Strategy recommended by World Health Organization (WHO) to control it was previously focused on school-aged children, but now preschool-aged children are involved. This study was intended to determine STH infection risk factors in preschool children. Methods A cross-sectional study was conducted in Suka Village, North Sumatera, Indonesia, from October to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 9 publications
5
32
2
9
Order By: Relevance
“…Our results show that children with untrimmed nger nails were more likely to be infected (p = 0.001) than those with trimmed nger nails. Our nding agree with previous studies (6,40,41). Increased risk of infection for children with untrimmed nger nails is because long nails can hide contamined soil obtained by child during play.…”
Section: Discussionsupporting
confidence: 94%
“…Our results show that children with untrimmed nger nails were more likely to be infected (p = 0.001) than those with trimmed nger nails. Our nding agree with previous studies (6,40,41). Increased risk of infection for children with untrimmed nger nails is because long nails can hide contamined soil obtained by child during play.…”
Section: Discussionsupporting
confidence: 94%
“…Our results show that children with untrimmed nger nails were more likely to be infected (p = 0.001) than those with trimmed nger nails. Our nding agree with previous studies (6,40,41). Increased risk of infection for children with untrimmed nger nails is because long nails can hide contamined soil obtained by child during play.…”
Section: Discussionsupporting
confidence: 93%
“…Humans are infected by ingesting infective eggs (Ascaris lumbricoides and Trichuris trichiura) or larvae (Ancylostoma duodenale) or skin penetration by infective larvae of hookworms (Necator americanus and Ancylostoma duodenale) in the soil (3,4). Heavy infections delays physical and cognitive development and interferes the body ability to respond to disease vaccines (5,6).…”
Section: Resultsmentioning
confidence: 99%
“…For reasons that they carry insignificant burden of worms. Other studies have found that PSAC have STH infection levels that may require them to be considered for regular treatment [37,38]. Nevertheless, in the recent years most deworming programmes have started including PSAC for treatment and control of STH.…”
Section: Discussionmentioning
confidence: 99%